ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA (STUDI PADA DEALER YAMAHA PT. UTAMA MEGAH SENTOSA BERSAUDARA) - Situmorang, Yohanes Lorens; Ferdinand, Augusty Tae (Faculty of Economics and Business Diponegoro University, 2017)
Transportation needs of motorcycles in Indonesia is increasing from year to year. And this is an opportunity for companies that offer motorcycle products to increase sales figures in various ways. This study aims to determine the effect of service quality product innovation, customer value and competitive pricing on purchasing decisions Yamaha brand motorcycles in the city Banjarbaru (a case study on consumer Yamaha Dealer